ANALISIS KUALITAS APLIKASI MYASN MENGGUNAKAN METODE USABILITY TESTING - Fernando, Jodhi Trio; Supratman, Edi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The purpose of this study is to measure the quality and usability of the MyASN application using the Usability Testing method. The measurement focuses on five aspects of usability, namely learning ability, efficiency, memory, errors, and satisfaction. This method was chosen because it is able to comprehensively describe the user experience, both in terms of ease of use and obstacles encountered when operating the application. The results show that the MyASN application obtained an overall usability score of 63%, which is categorized as “good.” This indicates that the application sufficiently meets the basic needs of civil servants in managing personnel data. However, there are still several aspects that need more serious attention, especially in terms of errors. Some users reported difficulties when navigating certain menus or errors when inputting data, which can reduce comfort and trust in the system. These findings have important implications that the development of the MyASN application should not only stop at achieving a good usability score, but also focus on improving the overall user experience.